Community-level foliar stable carbon isotope is dominantly influenced by leaf functional traits in dry Inner Mongolia steppes - Xu Wang; Yingying Bai; Shan Jiang; Kuan Li; Zhiyong Li; Huamin Liu; Lixin Wang; Yang Wang; Lei Dong; Cunzhu Liang; Jinghui Zhang (Communications Earth & Environment)
Abstract Foliar stable carbon isotope is an excellent indicator of plant water use efficiency, providing crucial insights into vegetation dynamics under climate change. However, in arid and semiarid grassland ecosystems, the factors driving variations in community-level foliar stable carbon isotope remain unclear. Here, we combined community-weighted mean foliar stable carbon isotope from 399 sampling sites across three grassland types in Inner Mongolia with environmental factors and leaf traits to reveal the mechanisms driving variations in community-level foliar carbon isotopes. We examined the impact of environmental factors (climate and soil factors) and leaf traits on community-level foliar stable carbon isotope. Our results show that community-level foliar stable carbon isotope variations are predominantly influenced by environmental factors in meadow and typical steppes but by leaf traits in desert steppe. These findings clarify divergent regulatory mechanisms of carbon-water balance in different grasslands, providing critical insights for predicting ecosystem responses to environmental changes.